Correlation between leptin level with lipid profile and free fatty acid in liver cirrhosis patients - Siti Nurdjanah, Siti Maryani, Neneng Ratnasari, (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Malnutrition is a common condition in liver cirrhotic patients. Leptin regulates body weightphysiologically by suppressing appetite and increasing energy expenditure. Leptin is higher in femalethan male. Studies have shown correlation between leptin with metabolic factors like body massindex (BMI) and lipid profile in cirrhotic patients. This study was conducted to investigate thecorrelation between serum leptin levels with lipid profile and free fatty acid in male patients with livercirrhosis. This was a cross sectional study that conducted at Gastroentero-Hepatology Clinic andInternal Ward at Dr. Sardjito General Hospital, Yogyakarta. The inclusion criteria were patients withliver cirrhosis > 18 years old, male, with Child-Pugh classification B and C, and provided informedconsent. The exclusion criteria were liver cirrhotic patients with comorbidity chronic kidney disease,chronic heart failure, diabetic, cancer, infection/septic, pregnancy, breast feeding, and steroid use.Data collecting was performed by anamnesis, physical examination, abdominal ultrasonographyexamination, and blood chemistry test. Pearson test was used to evaluate the correlation betweenthe serum leptin level with the lipid profile and free fatty acid. The results showed that no significantnegative correlation was observed between the serum leptin level with the total cholesterol (r= -0.052; p=0.766), high-density lipoprotein/HDL (r= -0.078; p=0.658) and triglyceride (r= -0.170; p=0.328) in male patients with liver cirrhosis. Furthermore, no significant positive correlationwas observed between the serum leptin levels with the low-density lipoprotein/LDL (r= -0.013; p=0.942) and free fatty acid/FFA (r= 0.007; p=0.968). In conclusion, there was no correlationbetween serum leptin levels with lipid profile and FFA in male patients with liver cirrhosis.